Exploring combustion chemistry of 1‐pentene: Flow reactor pyrolysis at various pressures and development of a detailed combustion model. Issue 4 (20th November 2020) - Cao, Chuangchuang; Li, Wei; Chen, Weiye; Ahmad, Hafiz; Yang, Jiuzhong; Li, Yuyang
Abstract: The pyrolysis of 1‐pentene was investigated in a flow reactor over temperatures of 900–1300 K and pressures of 0.04 and 1 atm using synchrotron vacuum ultraviolet photoionization mass spectrometry (SVUV‐PIMS). Pyrolysis products, especially radicals and cyclic compounds, were identified, and their mole fraction profiles were quantified. A detailed kinetic model of 1‐pentene combustion was developed and validated against the new data in this work. Modeling analysis including rate of production analysis and sensitivity analysis was performed to reveal the key pathways in the decomposition of 1‐pentene and the formation of pyrolysis products. Due to the presence of CC double bond in 1‐pentene molecule, the allylic CC bond dissociation reaction and the retro‐ene reaction play important roles in the formation of dominant pyrolysis products such as small alkenes. Besides, the formation of cyclic products including 1, 3‐cyclopentadiene, fulvene, benzene, and toluene is dominated by the reactions of C3 intermediates with C2 –C4 intermediates. The model was further validated against the previous data of 1‐pentene combustion, including the ignition delay times and laminar burning velocities over a wide range of pressures, temperatures, and equivalence ratios. Modeling analysis shows that C0 –C3 reactions and fuel‐specific reactions are important for the ignition process of 1‐pentene, while C0 –C2 reactions play significant roles in the laminar flame propagation of 1‐pentene.